Synthesis, characterization and antimicrobial activities of novel pyridinium salts - El-Shishtawy, Reda (Journal of King Abdulaziz University: Science, 2024)
New pyridinium salts containing sulfonamide were designed and synthesized with good yield. Different aryl sulfonyl chlorides were condensed with para-aminoacetophenone to afford the corresponding aryl-containing acetyl sulfonamide derivatives. Upon refluxing these compounds with pyridine in the presence of iodine, the corresponding pyridinium salts were obtained in good yield. Spectroscopic tools confirmed the chemical structures of the synthesized compounds. The antimicrobial activity of the newly synthesized compounds was evaluated to reveal that all compounds were structurally dependent- active against bacteria. On the other hand, testing these compounds as antifungals showed no activity. The results would further inspire structural modification for pyridinium-salt base antimicrobial agents.